Penerapan Model Pembelajaran Pengelolaan Usaha Boga - Priyanti, Priyanti; Khumaedi, Muhammad; Wijaya, M Burhan Rubay; Indani, Indani (Universitas Negeri Semarang, 2017)
Penelitian ini bertujuan untuk: Menguji keefektifan, kelayakan dan kepraktisan model yang dikembangkan. Penelitian ini menggunakan metode research and development (R&D). Model yang dikembangkan yaitu pembelajaran pengelolaan usaha boga.Â Studi pendahuluan dalam penelitian ini menunjukkan bahwa diperlukan tindak lanjut terhadap pembelajaran pengelolaan usaha boga untuk meningkatkan kompetensi wirausaha siswa. Model PPUB terbukti efektif dari adanya peningkatan hasil belajar siswa sebesar 0,371% kreteria â€œsedangâ€. Terbukti layak dari respon guru dengan rata-rata 3,25 kriteria â€œsangat layakâ€. Terbukti praktis dari respon siswa dengan rata-rata 3,4 kreteria â€œpraktisâ€. Dengan demikian model PPUB dapat meningkatkan kompetensi wirausaha siswa jasa boga. Saran agar hasil penelitian model perlu disosialisasikan kepada guru SMK Jasa Boga agar dapat diterapkan dalam pembelajaran pengelolaan usaha boga.This study aimed to determine: Testing the effectiveness, feasibility and practicality of the catering business management learning model which was developed. This study used Research and Development (R&D). The model that developed was the learning of catering business management. The preliminary study in this study indicated that follow-up to the learning of catering business management is required to improve the studentsâ€™ entrepreneurship competence. The development stage of catering business learning model included product design from learning media development and the strategy of learning model. The PPUB model proved that it was effective from the improvement of student learning outcomes by 0,371% with â€œmediumâ€ criteria. The PPUB model proved that it was feasible from the teacher responses with an average grade of 3.25 with â€œvery feasibleâ€ criteria, and the model proved that it was practical from the student responses by obtaining an average of 3.4 with â€œpracticalâ€ criteria. Thus, the model could improve studentsâ€™ entrepreneurs catering services competence. The suggestion from result of this study is model of PPUB needs to be socialized to the teachers of SMK Jasa Boga in order it can be apply in management of catering business learning